Major element analyses of plagioclase and pyroxene from gabbros of the layered mafic Dufek Intrusion - Grimes, Craig; Cheadle, Michael (IEDA: EarthChem Library, 2011)
Abstract: EMP analyses of plagioclase and pyroxene from gabbros sampled from the layered mafic Dufek Intrusion. The samples were collected in the austral summer 2006/2007 from the Dufek Massif, Forrestal Range, Pensacola mountains, Antarctica.